2021
DOI: 10.1002/cbin.11721
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hsp67Bc leads to autolysosome enlargement in the Drosophila brain

Abstract: Hsp67Bc is a small heat shock protein found in Drosophila melanogaster. Apart from performing a function (common for all small heat shock proteins) of preventing aggregation of misfolded proteins, it is involved in macroautophagy regulation alongside the Starvin protein. Overexpression of the D. melanogaster Hsp67Bc gene has been shown to stimulate macroautophagy in S2 cell culture. Nonetheless, it has been unknown how the absence of the Hsp67Bc gene may affect it. Here, we studied the effect of Hsp67Bc gene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Min and Benzer ( 48 ) found that Wolbachia can cause a widespread degeneration of tissues, including the brain and retina. Malkeyeva et al ( 49 ) reported that Wolbachia- induced a macro-autophagy in the neurons of D. melanogaster . However, without another probe for the CNS demonstrating co-localization of nervous tissue and Wolbachia , it is still unclear if there is a direct interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Min and Benzer ( 48 ) found that Wolbachia can cause a widespread degeneration of tissues, including the brain and retina. Malkeyeva et al ( 49 ) reported that Wolbachia- induced a macro-autophagy in the neurons of D. melanogaster . However, without another probe for the CNS demonstrating co-localization of nervous tissue and Wolbachia , it is still unclear if there is a direct interaction.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Wolbachia can cause degeneration of the retina and brain, and induce macro-autophagy in the neurons of D. melanogaster. 54,55 Some studies have shown that the memory retention of Trichogramma wasps is induced by Wolbachia infection. For example, memory duration is significantly shorter in Wolbachiainfected T. brassicae than in their uninfected counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have detected Wolbachia colonization in the central nervous system of host insects, including Folsomia candida , 47 Spalangia endius , 48 Drosophila melanogaster , 49,50 and Eurema hecabe , 51 and this may account for the effects of Wolbachia on host behaviors, including locomotion, sleep, feeding, mating preference and frequency, learning, and memory capacity 52,53 . Wolbachia can cause degeneration of the retina and brain, and induce macro‐autophagy in the neurons of D. melanogaster 54,55 . Some studies have shown that the memory retention of Trichogramma wasps is induced by Wolbachia infection.…”
Section: Discussionmentioning
confidence: 99%